Pengaruh Gaya Hidup, Persepsi Harga Dan Periklanan Terhadap Keputusan Pembelian Pada Rokok Sampoerna A Mild (Studi Kasus Pada Mahasiswa Fakultas Ekonomi Dan Bisnis Universitas Islam Malang Angkatan 2019) - Gery Rhivas Nugraha Wahyudi; N Rachma; Alfian Budi Primanto (E-JRM : Elektronik Jurnal Riset Manajemen, 2023)
Abstract The purpose of this study was to determine the effect of lifestyle, price perceptions and advertising on purchasing decisions on Sampoerna A Mild cigarettes (a case study of students at the Faculty of Economics and Business, Islamic University of Malang). This study used a quantitative research method using a questionnaire with a Likert scale of 1-5. The population in this study were students who consumed Sampoerna A Mild cigarettes. The data collection technique uses the techniquenonprobability sampling namely by techniquepurpose sampling. The sample in this study amounted to 95 respondents. The results of this study indicate that lifestyle has a significant effect on purchasing decisions, perceived price has no significant effect on purchasing decisions and advertising has a significant effect on purchasing decisions. Keywords: Lifestyle, Perceived price, Advertising and Purchase Decision